Modele logitowe satysfakcji zawodowej : analiza danych międzynarodowych - Kwiatkowska-Ciotucha, Dorota; Załuska, Urszula (Logistic Models of Job Satisfaction : International Data Analysis, 2006)
The aim of the analysis is identification of similarities and differences in the field of job-related satisfaction, and of the reasons (factors) influencing the job satisfaction level. The question is: how important for the satisfaction are demographic and social-economic features, such as age. gender, cohabitation status, occupation, industry, firm size. In order to achieve the formulated research goal, the multidimensional statistical analysis framework was used for analysis of the selected information contained in the ECHP database - European Community Household Panel (involving approximately 150.000 respondents from 15 "old" EU members).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (16); 2006; nr 1100, s. 183-192